Development of Hypercontent-Based PMR Media to Improve Students' Mathematics Problem Solving Abilities and Learning Independence - Manihuruk, Hermanto; Mulyono, Mulyono; Nasution, Hamidah (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2024)
This research aims to analyze the validity, practicality, and effectiveness of PMR-based mathematics learning tools assisted by hypercontent developed to improve class VIII students' mathematical problem-solving abilities and learning independence at SMP N 1 Jorlang Hataran.. This research method is a type of development research using ADDIE learning tools. The place and time of the research was carried out at SMP N 1 Jorlang Hataran in the even semester of the 2022/2023 academic year on the subject of the Pythagorean Theorem. The subjects in this research were students in class VIII-3 of SMP N 1 Jorlang Hataran for the 2022/2023 academic year with a total of 32 students, while the object of this research was a learning tool developed based on a realistic mathematics approach assisted by hypercontent to improve problem solving abilities and learning independence. students on Pythagorean theorem material. Research result; The PMR-based mathematics learning device assisted by hypercontent that was developed was declared valid, practical and effective; the increase in mathematical problem solving abilities and learning independence of class VIII students at SMP N 1 Jorlang Hataran through the PMR-based mathematics learning device assisted by hypercontent that was developed was stated to have increased. Research and development of devices using the ADDIE model can be used as an alternative for developing devices for mathematics subjects because the ADDIE model is very easy to implement and the steps for implementing the development are very clear and structured.